On some identities involving certain Hardy sums and Kloosterman sum - Dağlı, M. C. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 511 We give a new reciprocity theorem for the Hardy sum s_5(h,p). Also, a hybrid mean value problem involving the Hardy sum s_4(h,p) and Kloosterman sum is studied and two exact computational formulae are obtained.